A new strategy for professional medical support couples with infertility - O. B. Zhukov; V. V. Evdokimov; A. A. Zhukov; L. H. Shugusheva; E. E. Bragina (Андрология и генитальная хирургия, 2014)
From our point of view, the problem of infertility in a pair of appropriately addressed jointly by the two related disciplines. This process has been actively helping set newsupplements Spematon and Pregnoton. The study included 50 couples planning to conceive: 25 couples with male factor infertility secretory type (group 1), 25 couples with infertility caused by varicocele in the postoperative period (group 2). The first group included patients with hyperprolactinemia relative to a second group – 25 somatically healthy patients. All groups patients takes Spematon and Pregnoton during 3 months. Terms of infertility in couples ranged from 1 to 4,5 years and an average reached 2,8 ± 1,6 years. According to the results of the comparative analysis the reproductive value of sperm had been enhanced, functional status of the female reproductive system had been improved, the menstrual cycle had been normalized and relatively elevated levels of prolactin had been decreased after co-application of these supplements. Five woman became pregnant.